Praktik Perawatan Kehamilan dan Persalinan Kelompok Ibu Hamil di Wilayah Kerja Puskesmas Melolo, Kecamatan Umalulu, Sumba Timur (Sunari Penjor : Journal of Anthropology, 2025)
This study aims to understand the practice of pregnancy and childbirth care carried out by pregnant women in the working area of the Melolo Health Center, Umalulu District, East Sumba. This research uses qualitative research methods with an interpretive descriptive approach. The theory used in this study is the theory of health care systems by Foster and Anderson, used to understand and explain the behavior of pregnancy and childbirth care through modern and traditional medical care systems. The results showed that the health behaviors carried out by pregnant women in the Melolo Health Center work area mostly mixed pregnancy care methods recommended or recommended by birth attendants while still checking themselves regularly at available health facilities.
Keywords: Pregnancy and Maternity Care; Pregnant Mother; Puskesmas Melolo